Treatment of diffuse large B‐cell lymphoma with secondary central nervous system involvement: encouraging efficacy using CNS‐penetrating R‐IDARAM chemotherapy. (18th December 2015) - Maciocia, Paul; Badat, Mohsin; Cheesman, Simon; D'Sa, Shirley; Joshi, Rahul; Lambert, Jonathan; Mohamedbhai, Sajir; Pule, Martin; Linch, David; Ardeshna, Kirit
Summary: Diffuse large B‐cell lymphoma with secondary involvement of the central nervous system (SCNS‐DLBCL) is a rare condition carrying a poor prognosis. No optimal therapeutic regimen has been identified. We retrospectively analysed 23 patients with SCNS‐DLBCL treated with R‐IDARAM (rituximab 375 mg/m 2 IV day 1; methotrexate 12·5 mg by intrathecal injection day 1; idarubicin 10 mg/m 2 /day IV days 1 and 2; dexamethasone 100 mg/day IV infusion over 12 h days 1–3; cytosine arabinoside 1000 mg/m 2 /day IV over 1 h days 1 and 2; and methotrexate 2000 mg/m 2 IV over 2 h day 3. Ten out of 23 (44%) patients had CNS involvement at initial presentation ('new disease'), 10/23 (44%) had relapsed disease and 3/23 (13%) had primary refractory disease. 14/23 (61%) of patients responded ‐ 6 (26%) complete response, 8 (35%) partial response. Grade 3–4 haematological toxicity was seen in all cycles, with no grade 3–4 or long‐term neurological toxicity. Median follow‐up for surviving patients was 49 months. At 2 years, estimated progression‐free survival (PFS) was 39% and overall survival (OS) was 52%. Encouraging outcomes were reported in patients with new disease, with 5‐year estimated PFS of 50% and OS 75%. R‐IDARAM is a well‐tolerated regimen with encouraging efficacy in patients with SCNS‐DLBCL, although patients with relapsed or refractory disease continue to fare poorly.